1962. TRAIL Level and ImmunoXpert™ Score Complement Molecular Viral Detection in the Classification of Febrile Children: An Interim Analysis From the AutoPilotDx-Study. (26th November 2018) - Tenenbaum, Tobias; Papan, Cihan; Porwoll, Marian; Hakim, Ummaya; Argentiero, Alberto; Testa, Ilaria; Pasticci, Maria Bruna; Mezzetti, Daniele; Perruccio, Katia; Etshtein, Liat; Mastboim, Niv; Cohen, Asi; et al.
Abstract: Background: Differentiating between viral and bacterial etiology is essential in order to enable the adequate use of antibiotics. Previous studies showed that TNF-related apoptosis induced ligand (TRAIL) can serve as a useful biomarker for distinguishing between bacterial and viral infections when combined with IP-10 and CRP (ImmunoXpert™). Here we evaluate the potential of a new proteomic fingerprints in children with suspected viral and bacterial infections that had a confirmed viral detection. Methods: In the prospective multinational multicenter study "AutoPilot-Dx" (NCT03052088) we aim to validate the diagnostic accuracy of the ImmunoXpert™ test. Infection etiology was assigned by majority adjudication of three experts based on comprehensive clinical and laboratory investigation. Viruses were detected using multiplex-PCR applied to nasopharyngeal swabs (Allplex™, Seegene). We performed an interim analysis of the first 134 febrile children recruited that had both PCR viral detection and etiology determination. TRAIL, IP-10, CRP and ImmunoXpert™ values were measured via a Tecan EVO75 ELISA platform. Results: Bacterial diagnoses were assigned by the experts to 29%, 29% and 25% of patients with adenovirus (ADV), rhinovirus (RV), and respiratory syncytial virus (RSV) detection, respectively. Children with a viral infection including ADV, RSV, and RV had significantly lower ImmunoXpert™ scores as compared with children with a bacterial infection. Notably, TRAIL levels were markedly increased in viral infections as compared with bacterial infection, irrespective of the detected virus. Conclusion: Classification of viral infections correlated significantly with elevated TRAIL levels and low ImmunoXpert™ scores. The differential expression of TRAIL in response to viral vs. bacterial infections can complement molecular viral detection, appears useful in the diagnostic workup for febrile children and may reduce antibiotic misuse. Disclosures: L. Etshtein, MeMed Diagnostics: Employee, Salary. N. Mastboim, MeMed Diagnostics: Employee, Salary. A. Cohen, MeMed Diagnostics: Employee, Salary. E. Simon, MeMed: Employee, Salary. O. Boico, MeMed Diagnostics: Employee, Salary. L. Shani, MeMed Diagnostics: Employee, Salary. T. Gottlieb, MeMed Diagnostics: Employee, Salary. R. Navon, MeMed Diagnostics: Employee, Salary. K. Oved, MeMed Diagnostics: Board Member, Employee and Shareholder, Salary. E. Eden, MeMed Diagnostics: Board Member, Employee and Shareholder, Salary.